VALIDASI BAHAN AJAR PENGUATAN KARAKTER BERBASIS KEARIFAN LOKAL KAWASAN PESISIR LOMBOK - Septiana Dwi Utami; Ika Nurani Dewi; Sri Nopita Primawati (JUPE : Jurnal Pendidikan Mandala, 2022)
Abstract. The urgency of this research refers to the context of strengthening the profile of Pancasila students which is currently important to do to maintain local wisdom values. The formation and strengthening of character needs to be instilled from an early age so that in the future they become Indonesian people who have local character and have a global perspective. Teaching materials can be used as an alternative learning resource to convey messages about the character of Pancasila student profiles and to train students' literacy skills. Several previous studies related to the development of teaching materials are believed to be able to improve students' superior competence, but still need improvement by adding character strengthening features in the developed teaching materials. In addition, science education has an important contribution in preparing Indonesian human resources with character and 21st century skills as agents of change for the nation. Therefore, innovation is needed in the development of character strengthening teaching materials based on local wisdom in the Lombok coastal area to form a profile of Pancasila students. This research is product-oriented development research in the field of education. This study uses the ADDIE development design which consists of Analyze, design, develop, implement, and Evaluate. Based on the results of research on the development of student activity sheets (LKS) strengthening character based on local wisdom in the Lombok coastal area concluded that the validator's assessment was stated to be very valid for format aspects (84%), material (85.7%), language (86.1%), Assessment LKS in supporting innovation and improving the quality of teaching and learning activities (86.4%) while presentation (77%). Keywords: Teaching Material Validation, Based on Local Wisdom, Lombok Coastal Area Abstrak. Urgensi penelitian ini mengacu pada konteks penguatan profil pelajar pancasila yang saat ini penting dilakukan untuk mempertahankan nilai-nilai kearifan lokal. Pembentukan dan penguatan karakter perlu ditanamkan sejak dini sehingga kelak menjadi manusia Indonesia yang memiliki karakter lokal dan berwawasan global. Bahan ajar dapat dijadikan sebagai salah satu sumber belajar alternatif untuk menyampaikan pesan karakter profil pelajar pancasila serta  melatih  keterampilan literasi  siswa.  Beberapa penelitian  terdahulu  terkait pengembangan bahan ajar diyakini dapat meningkatkan kompetensi unggul siswa, namun masih perlu penyempurnaan dengan menambahkan fitur penguatan karakter dalam bahan ajar yang dikembangkan. Selain itu, pendidikan IPA memiliki kontribusi penting dalam mempersiapkan SDM Indonesia yang berkarakter dan memiliki kecakapan abad 21 sebagai agen perubahan bangsa. Oleh sebab itu, dibutuhkan inovasi dalam pengembangan bahan ajar penguatan karakter berbasis kearifan lokal kawasan pesisir Lombok   untuk membentuk profil pelajar Pancasila. Penelitian ini adalah penelitian pengembangan yang berorientasi pada produk dalam bidang pendidikan. Penelitian ini menggunakan desain pengembangan ADDIE yang terdiri dari Analyze, desing, development, implement, dan Evaluate. Berdasarkan hasil penelitian pengembangan lembar kegiatan siswa (LKS) penguatan karakter berbasis kearifan lokal kawasan pesisir Lombok menyimpulkan bahwa penilian validator dinyatakan sangat valid untuk aspek  format (84%), materi (85,7%), kebahasaan (86,1%), Penilaian LKS dalam menunjang inovasi dan peningkatan mutu kegiatan belajar mengajar (86,4%) sedangkan penyajian (77%). Kata Kunci: Validasi Bahan Ajar, Berbasis Kearifan Lokal, Kawasan Pesisir Lombok